1994
DOI: 10.1111/j.1476-5381.1994.tb13032.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the endothelin ETA receptor antagonist, FR 139317, on infarct size in a rabbit model of acute myocardial ischaemia and reperfusion

Abstract: 1 The effects were investigated of the ETA receptor antagonist, FR 139317, on endothelin-1 (ET-1)-induced coronary vasoconstriction in the isolated perfused heart of the rabbit. In addition, this study examined whether FR 139317 reduced infarct size in a rabbit model of coronary artery occlusion and reperfusion.2 In the rabbit isolated perfused heart, ET-1 (1-100pmol) elicited a dose-dependent increase in coronary perfusion pressure (CPP). For example, 30 pmol ET-1 caused CPP to rise by 22 ± 8 mmHg and 100 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…However, recent studies with ETA antagonists provided controversial results: continuous i.v. injection of BQ-123 reduced the infarct size in dogs (Grover et al, 1993), while that of FR139317 showed no effects in rabbits (McMurdo et al, 1994). Since monoclonal antibody for ET-1 reduced the infarct size in rats (Watanabe et al, 1991), rabbits (Kusumoto et al, 1993) and dogs (unpublished observations), species-dependency is not likely to be the explanation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, recent studies with ETA antagonists provided controversial results: continuous i.v. injection of BQ-123 reduced the infarct size in dogs (Grover et al, 1993), while that of FR139317 showed no effects in rabbits (McMurdo et al, 1994). Since monoclonal antibody for ET-1 reduced the infarct size in rats (Watanabe et al, 1991), rabbits (Kusumoto et al, 1993) and dogs (unpublished observations), species-dependency is not likely to be the explanation.…”
Section: Discussionmentioning
confidence: 94%
“…These receptor subtypes showed different sensitivities Author for correspondence. to the three endothelin isoforms so that ET-1 and ET-2 had high, almost equal, affinities for both ETA and ETB receptors (Sakurai et al, 1990), whereas ET-3 had a higher affinity for ETB than ETA receptors (Arai et al, 1990). Although ETA and ETB receptors were originally assigned to be responsible for ET-1-induced vasoconstriction and vasorelaxation, respectively (Masaki et al, 1992), it has been demonstrated that both receptor subtypes were involved in ET-1-induced vasoconstriction (Sumner et al, 1992;Clozel et al, 1992) as well as hypertension (McMurdo et al, 1993 antagonists, such as BQ-123 (Ihara et al, 1992), FR139317 (Sogabe et al, 1993), IRL1038 (Urade et al, 1992) and Ro 46-2005 (Clozel et al, 1993) (Mino et al, 1992) and by subarachnoid haemorrhage (Clozel et al, 1993) (Grover et al, 1993), whereas FR139317 did not in rabbits (McMurdo et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…This is not entirely surprising, as in rabbits subjected to regional myocardial ischaemia, an increase in the length of the reperfusion period from 2 to 8 h does not result in a signi®cant further increase in infarct site in the rat. This is not entirely surprising as in rabbits subjected to regional myocardial ischaemia, an increase in the length of the reperfusion period from 2 to 8 h does also not result in a signi®cant further increase in infarct size (McMurdo et al, 1994). In addition to measuring myocardial cell necrosis by NBT-staining or histology, the determination of the plasma levels of enzymes which are released by cardiac myocytes may also be used as a reliable indicator of tissue necrosis.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the mixed ETA/ETB receptor antagonist TAK-044 showed a limited inhibitory effect on the extension of infarct size in rats [16], whereas BQ-123 (ETA receptor antagonist) was without effect in the same model [17]. Another ETA receptor antagonist, FR 139317 was without effect in a rabbit model of ischemia/reperfusion [18], and led to an increase, rather than a decrease in infarct size in dogs [19]. Our results may be of relevance to these discrepancies.…”
Section: Discussionmentioning
confidence: 99%